Differential age-related effects on conjunctive and relational visual short-term memory binding. Issue 9 (21st October 2018) - Bastin, Christine
ABSTRACT: An age-related associative deficit has been described in visual short-term binding memory tasks. However, separate studies have suggested that ageing disrupts relational binding (to associate distinct items or item and context) more than conjunctive binding (to integrate features within an object). The current study directly compared relational and conjunctive binding with a short-term memory task for object–colour associations in 30 young and 30 older adults. Participants studied a number of object–colour associations corresponding to their individual object span level in a relational task in which objects were associated to colour patches and a conjunctive task where colour was integrated into the object. Memory for individual items and for associations was tested with a recognition memory test. Evidence for an age-related associative deficit was observed in the relational binding task, but not in the conjunctive binding task. This differential impact of ageing on relational and conjunctive short-term binding is discussed by reference to two underlying age-related cognitive difficulties: diminished hippocampally dependent binding and attentional resources.